ANALISIS PENGARUH PEMBIAYAAN DAERAH, BELANJA TIDAK TERDUGA DAN BELANJA SUBSIDI TERHADAP PERTUMBUHAN EKONOMI DI INDONESIA MENGGUNAKAN MODEL ARDL - Mahdalena, Sonia Santa; Ichsan, Ichsan (LPPM UNIMAL, 2023)
This study aims to analyze the effect of Regional Financing, Unexpected Expenditures, and Subsidy Expenditures on economic growth in Indonesia. The data used is secondary data for 1990-2021 accessed from the Indonesias Central Bureau of Statistics and the World Bank. The data analysis method used is Autoregressive Distributed Lag (ARDL) using Eviews 10 software. The results of this study indicate that in the estimation of the ARDL model, in the short term Regional Financing and Unexpected Expenditures are not detected. In the short term at lag 0, Lag 1, and Lag 2 Subsidy spending has a negative and significant effect on economic growth in Indonesia. Meanwhile, in lag 3 Subsidy Spending has a positive and significant effect on economic growth in Indonesia in the current year. In the long term Subsidy Expenditures do not have a significant effect on economic growth in Indonesia. Based on the results of this study, it is suggested that the government conduct better management of subsidy spending so that it is right on target, so that it can encourage more optimal economic growth.